2012
DOI: 10.1364/oe.20.024949
|View full text |Cite
|
Sign up to set email alerts
|

Active aberration- and point-spread-function control in direct laser writing

Abstract: We control the point-spread-function of high numerical aperture objectives used for direct laser writing with a spatial light modulator. Combining aberration correction with different types of amplitude filters to reduce the aspect ratio of the point-spread-function enhances the structural and optical quality of woodpile photonic crystals. Here, aberration correction is crucial to ensure the functionality of the filters. Measured point-spread-functions compare well with numerical calculations and with structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…[ 56,57 ] Despite the sequential update of the digital hologram displayed on the SLM, smooth structuring was demonstrated (Figure 2 h). [ 34,[59][60][61][62] [ 58 ] Aberrations may severely degrade the energy confi nement in the focus leading to a strong reduction of structural quality.…”
Section: Slm-based Laser Lithographymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 56,57 ] Despite the sequential update of the digital hologram displayed on the SLM, smooth structuring was demonstrated (Figure 2 h). [ 34,[59][60][61][62] [ 58 ] Aberrations may severely degrade the energy confi nement in the focus leading to a strong reduction of structural quality.…”
Section: Slm-based Laser Lithographymentioning
confidence: 99%
“…[ 67 ] However, due to the lower confi nement along one axis, proximity effects are increased. [ 62 ] In the same publication it was shown that the reduced aspect ratio leads to a larger fabrication window of these photonic structures and in consequence to improved structural quality. The reduction of the aspect ratio may also be achieved by shaded-ring fi lters.…”
Section: Progress Reportmentioning
confidence: 99%
“…This eliminated interference with unmodulated light from the SLM allowing effective control of the intensity and phase distribution of light in the pupil plane of the objective lens [19]. In this configuration, the SLM could be used for adaptive aberration correction and beam shaping [20,21], greatly improving the quality of the fabrication focus.…”
Section: Introductionmentioning
confidence: 99%
“…For most 3D PhCs suitable for the commercially relevant 1.55 μm wavelength, the desired voxel aspect ratio is 1. In future work, we will investigate various ways to reduce this ratio, including the use of a spatial light modulator (SLM) for adaptive beam shaping and dark field illumination schemes [36,37]. The stimulated emission depletion (STED) technique [38,39] could also be configured to improve aspect ratio although is best for improving lateral resolution.…”
Section: Discussionmentioning
confidence: 99%